Effect of polyacrylamide on rheology of fresh cement pastes. (October 2015) - Bessaies-Bey, Hela; Baumann, Robert; Schmitz, Marc; Radler, Michael; Roussel, Nicolas
Abstract: In this paper, we study the effects of polyacrylamide (PAM) on both aqueous solutions and fresh cement pastes. Our solution viscosity and hydrodynamic radii measurements in various solutions suggest that calcium ions lead to a cross-linking of anionic PAM and to the formation of PAM micro-gels. Our adsorption measurements show that the majority of these micro-gels adsorb on cement grains whereas our rheological measurements on cement pastes suggest that these micro-gels are able to adsorb simultaneously on several cement grains and bridge them increasing therefore the macroscopic yield stress of the suspension. Finally, we show that the contribution of PAM to yield stress is very sensitive to shear history, as the paste structure seems to progressively lose its ability to rebuild with each shearing or re-mixing cycle. We suggest that this feature could find its origin in the progressive flattening of the micro-gels at the surface of the cement grains. Highlights: We measure the rheology of various aqueous ionic solutions containing polyacrylamide. We measure the hydrodynamic radii of polyacrylamide using DLS in various aqueous solvents. We suggest that calcium ions are able to cross-link polyacrylamide chains and form micro-gels. We measure adsorption isotherms of polyacrylamide on cement grains. We suggest that polyacrylamide micro-gels do bridge cement grains and increase the yield stress of cement pastes.